2009
DOI: 10.1105/tpc.108.062158
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinases 3 and 6 Are Required for Full Priming of Stress Responses inArabidopsis thaliana   

Abstract: In plants and animals, induced resistance (IR) to biotic and abiotic stress is associated with priming of cells for faster and stronger activation of defense responses. It has been hypothesized that cell priming involves accumulation of latent signaling components that are not used until challenge exposure to stress. However, the identity of such signaling components has remained elusive. Here, we show that during development of chemically induced resistance in Arabidopsis thaliana, priming is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
382
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(406 citation statements)
references
References 60 publications
9
382
0
5
Order By: Relevance
“…For instance, MPK3 is an important regulator of benzothiadiazole-induced priming of defense gene activation, while MPK6 appears to play a minor role in this response (Beckers et al, 2009). Furthermore, MPK6 has a stronger effect on the up-regulation of genes involved in camalexin biosynthesis that are induced by the expression of a constitutively active MAPKKK, while MPK3 plays a major role in camalexin accumulation and disease development during B. cinerea infection (Ren et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, MPK3 is an important regulator of benzothiadiazole-induced priming of defense gene activation, while MPK6 appears to play a minor role in this response (Beckers et al, 2009). Furthermore, MPK6 has a stronger effect on the up-regulation of genes involved in camalexin biosynthesis that are induced by the expression of a constitutively active MAPKKK, while MPK3 plays a major role in camalexin accumulation and disease development during B. cinerea infection (Ren et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to MPK4, increasing evidence indicates that MPK3 and MPK6 exert a positive role on the activation of Arabidopsis defense responses. For instance, they have been shown to regulate camalexin accumulation (Ren et al, 2008) and ethylene (ET) production during fungal infection, and to be required for chemically induced priming of stress responses (Beckers et al, 2009).…”
mentioning
confidence: 99%
“…Instead, an accelerated activation of plant defenses occurs upon pathogen recognition, providing a stronger and faster defense response. Possible mechanisms of priming in SAR and ISR involve the expression of signaling components such as transcription factors , 2009, or the activation of protein kinases such as MAPK3 and MAPK6 (Beckers et al 2009), which stay inactive until pathogen recognition. Another mechanism behind priming appears to be a change in chromatin structure (Bruce et al 2007; Van den Burg and Takken 2009).…”
Section: Activation Of Plant Inducible Defense Responsesmentioning
confidence: 99%
“…MAPK signaling is mediated at the transcriptional, translational, and posttranslational levels (Beckers et al, 2009) and was for instance shown to promote the synthesis of camalexin, an antimicrobial compound (Ren et al, 2008). MAPKs also participate in signal transduction leading to transcriptional reprogramming of defense-related genes (Fiil et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Poplar MAPKs were shown to be activated in response to chitosan, ozone treatment, and following infection by Melampsora foliar rust (Hamel et al, 2005;Boyle et al, 2010), yet no downstream substrate has been identified. Based on these data, and given the importance of AtMPK3 (and its orthologs) in both the priming (Beckers et al, 2009) and regulation of defense mechanisms against bacteria and fungi (Asai et al, 2002;Ren et al, 2008), a yeast two-hybrid screen was performed to find putative interactors of poplar PtiMPK3-1. This approach allowed the identification of a novel MAPK-interacting protein, PtiZFP1, a TF that belongs to the Cys-2/His-2-type zinc finger protein family and that is characterized by the presence of an ERF-associated amphiphilic repression (EAR) motif at the C terminus.…”
mentioning
confidence: 99%